Hydro-upgrading of bio-oils derived from pyrolysis of biomass with different H/Ceff ratios in tetralin over Pt/C and Ru/C. (1st March 2023) - Wang, Zhi-Cong; Duo, Jia; Shan, Ya-Qi; Yin, Lin-Xin; Duan, Pei-Gao
Abstract: Pyrolysis oils with different effective hydrogen (H/Ceff ) ratios are mixed with tetralin at a mass ratio of 1:1 and treated at 400 °C for 2 h under 6 MPa H2 over Pt/C and Ru/C, respectively, to examine the effect of H/Ceff ratio on the yield and quality of the upgraded oil. Pyrolysis oil with higher H/Ceff ratios results in an upgraded oil with higher yield and H/Ceff ratios. The highest S and O reduction ratios of 96.11% and 56.26% are achieved with added Pt/C at an H/Ceff ratio of 1.39 of the feedstock. In comparison, the highest N reduction ratios of 34.50% is achieved with added Ru/C at an H/Ceff ratio of 1.38 of the feedstock. The N and S poison the catalyst's active sites and reduce the deoxygenation efficiency. Thus, we view that the H/Ceff plays a vital role in improving the properties of the bio-oil. Highlights: Effective hydrogen significantly affected the yield and quality of the pyrolysis oil. Higher effective hydrogen of biomass resulted in pyrolysis oil with higher effective hydrogen. Higher effective hydrogen of pyrolysis oil resulted in upgraded oil with higher effective hydrogen. The presence of N in the pyrolysis oil impaired the O and S removal from the pyrolysis oil. Better performance of platinum than ruthenium was observed toward the N, O, and S removal.